Funding of the political parties in Western Europe - Bložė, Mindaugas (Politologija, 1999)
In this article the author researches and analyses one of the most immediate issues the political parties of every country face—that of the funding of the political parties. Their self-dependence and the politics they choose to declare in general are made dependent on how the given issue is resolved. This article is a minor to such well-known monographies like H. H. von Arnim's monography Party Funding, State Funding of the Parties without Control as well as The New Party Funding. As guidelines the author treats the researches committed by P. Lösche, G. Werwéris (monographies), G. Klee Kruse, K.-H. Nassmacher, as well as the elaborate study of the European Union's parties accomplished by D. To. Tsatsos.In this article the author overviews the legislative basis regulating the funding of the political parties, the shape and sources of funding, state and social mechanisms of the party funding, as well as presents the reaction of the parties to the issue themselves. Author sets the purpose of the article—to discuss history pertinent to political party funding in the West European countries, especially those, which can be classified as multiparty. For the sake of the accomplishment, the author endorses six West European countries, starting from Denmark, France, Germany, Ireland, Italy, and ending with the Netherlands.Save using the factual data provided by Western politologists, in this article the following conclusions are drawn: first, in the aforementioned countries the legislature regulating the funding of political parties was passed very late—not earlier than in the 60s and 70s. In Western countries four models of funding can be clearly distinguished:non-state funding;mixed funding;state funding; andforeign funds.Author notes that each of the given models of funding can be financed from different sources. However, none of the first three models by far played a decisive or an outstanding role in the financial life of the political parties. The fourth model—that is, foreign funds—is nowadays in every country little but completely meaningless, plus—formally banned.The author comes to emphasize one crucial point—in every country referred to, the budgets of the political parties augment rapidly.When the legislation regulating the funding of the political parties was passed it pressed the parties to execute strict financial accountancy and controls. The control of the party funds is executed by the parties themselves, authorized government, and other control institutions. The legislation, which had introduced the controls on the funds, was met by the parties differently, with differing arguments. Notwithstanding the initial goal of the legislation—to strengthen the self-dependence and equal rights of the political parties, and deter the possibility of monopolization by one—the goals were not accomplished to the end. It emerged that the strongest parties were better fit to live the party-funding legislation. On their side, the popularity of small and marginal parties declined; in some places, the appearance of the new legislation and further developments had made the overall membership of the parties shrink.
Keywords: -